Effect of Pineapple Juice on Perineal Wound Healing in Postpartum Mothers at Anugrah Clinic - Farida Umamy; Isma Adelina Harahap; Meity Christiani (Institute of Computer Science (IOCS), 2021)
One solution for postpartum mothers to accelerate the healing of perineal wounds is natural herbs with the application of pineapple juice to help accelerate the healing of perineal wounds. The purpose of this study was to determine the effect of pineapple juice on perineal wound healing at Anugrah Clinic. An experimental method with a post-test-only control group design approach. The subjects of this study were postpartum mothers with grades I and II perineal tears. The sample is 20 people with an accidental sampling technique. Data analysis used univariate analysis test and bivariate test with Mann-Whitney U. The data obtained from the results of the study showed that the healing of perineal wounds in the group that was not given pineapple juice was mostly (70%) healed within 7-10 days and none experienced faster healing. While in the group given pineapple juice as much as 60% experienced faster healing, which was less than 7 days, and 40% of respondents who consumed pineapple juice recovered within 7-10 days. The results of statistical data analysis using Mann- Whitney U obtained a Z value of -3.033 with a p-value of 0.002 (p<0.05), then H0 was rejected, which means that consumption of pineapple juice has a significant effect on perineal wound healing at Anugrah Clinic. Support from health workers, especially midwives, is expected to help mothers go through the postpartum period, especially for mothers who have injuries to the perineum. Giving pineapple juice can be an alternative to accelerate wound healing in the perineum.